2 Peter and the Apocalypse of Peter : towards a new perspective : Radboud prestige lectures by Jörg Frey - Frey, Jörg, (Biblical Interpretation Series, 2019)
In the 2016 Radboud Prestige Lectures , published in this volume, Jörg Frey develops a new perspective on 2 Peter by arguing that the letter is dependent on the Apocalypse of Peter . Frey argues that reading 2 Peter against the backdrop of the Apocalypse of Peter sheds new light on many longstanding interpretative questions and offers fresh insights into the history of second-century Christianity. Frey's lectures are followed by responses from leading scholars in the field, who discuss Frey's proposal in ways both critical and constructive. Contributors include: Richard Bauckham, Jan Bremmer, Terrance Callan, Paul Foster, Jeremy Hultin, Tobias Nicklas, David Nienhuis and Martin Ruf.